(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of infertility, hirsutism and acne in patients of PCOS and compare it with the body mass index(BMI) of the subjects. Study Design: Cross-sectional, descriptive study. Place and Duration of Study: This study was conducted at the Outpatient Department of Obstetrics and gynecology, Mardan medical Complex Teaching Hospital from January 2017 to October 2017. Materials and Methods: This study was conducted on 250 patients of Polycystic Ovarian Syndrome. Frequency of infertility, hirsutism and acne was compared with the body mass index(BMI). Diagnosis of Polycystic Ovarian Syndrome was done on the basis of 2003 Rotterdam diagnostic criteria.FerrimanGallwey scorewas used for assessment of hirsutism and WHO cut-offs of Body Mass Indexmodified for Asian population was used for assessment of Body mass index. Results: Ofthe total 250 patients with Polycystic Ovarian Syndrome,the mean age was 25.63± 4.44 years and the mean BMI was 30.12±6.63 Kg/m2. The frequency of infertility, hirsutism and acne was 64 % (n=151), 72.8 % (n=182) and32 % (n=80) respectively and all had a statistically significant association with obesity.The frequency of obesity in those with infertility, hirsutism and acne was 80.6 %, 89.02 % and 90 % respectively. Conclusion: Hirsutism, infertility and acne were significantly common in patients with Polycystic Ovarian Syndrome and most of the patients were pre-obese as per WHO cut-offs of Body Mass Index for Asian population.